University Student’s Academic Scheduler - Hafit, Hanayanti; Chai Long Hui , (Applied Information Technology And Computer Science, 2020)
The current existing application does not specialized for university students’ need in schedule tasks and events within a single place. This project is to design and develop then test a new android mobile application that specialized for university students which help them to schedule task. The application is developed using the Object-Oriented (OO) concept and implemented using the Java programming language. Academic scheduler for university students may help university students scheduling their tasks. Hence, it may be a way of resolving the task scheduling problem faced by university students.